Incidence, duration, and reappearance of type-specific cervical human papillomavirus infections in young women (2010)
Background: We describe the incidence and duration of cervical human papillomavirus (HPV) infection episodes along with the risk of infection reappearance following a period of nondetection. Methods:Women (1,788) ages 16 to 23 years underwent cytologic testing and PCR-based testing of cervical swab samples for HPV DNA (HPV-16/18/31/33/35/45/52/58/59) at ?6-month intervals for up to 4 years in the context of a phase 3 clinical trial (placebo arm). HPV type - specific incidence rates were estimated per 100 person-years. Duration of type-specific cervical infection episodes and risk of reappearance following a period of nondetection were estimated using Kaplan-Meier methods. Results: HPV-16 exhibited the highest (5.9), and HPV-35 and HPV-33 exhibited the lowest (1.0) incidence rates per 100 person-years. Mean cervical infection durations ranged from 13 months for HPV-59 to 20 months for HPV-16 and 58 (with ongoing infections censored at the time of treatment, if done). The risk of cervical infection reappearance within ?3 years following a period of nondetection ranged from 0% to 16% across HPV types, with a mean of 8%. Limited evidence was found for a role of false-positive HPV tests, missed infections that were above the threshold for detection, or new acquisition of infection in accounting for patterns of infection reappearance. Conclusions: Incidence of high-risk cervical infection was observed to vary considerably more across HPV types than infection duration. A nontrivial proportion of women exhibited infection reappearance following a period of nondetection, with a potential explanation for many such events observed within this analysis being a return to detectable levels of a previously acquired infection. Impact: The risk of HPV infection reappearance following a period of nondetection has not been previously reported for individual HPV types, and this study finds that a nontrivial proportion of infected women exhibit reappearances. Future studies could ascertain subject-level factors that potentially modify the risk of infection reappearance. ©2010 AACR.